Herbal formula GAPT prevents beta amyloid deposition induced Ca2+/Calmodulin-dependent protein kinase II and Ca2+/Calmodulin-dependent protein phosphatase 2B imbalance in APPV717I mice. Issue 1 (December 2016) - Shi, Jing; Zhang, Xuekai; Yin, Long; Wei, Mingqing; Ni, Jingnian; Li, Ting; Wang, Pengwen; Tian, Jinzhou; Wang, Yongyan
Abstract Background Synaptic dysfunction is one of the pathological characteristics of Alzheimer's disease (AD), which is directly related to the progressive decline of cognitive function. CaMKII and CaN have been found to play important roles in memory processes and synaptic transmission. So present study aimed to elucidate relationships between CaMKII, CaN and cognitive decline in APPV717I mice, and to reveal whether the cognitive improving effects of GAPT is conducted through rebalance CaMKII and CaN. Methods Three-month-old-male APPV717I mice were randomly divided into ten groups (n  = 12 per group) and received intragastrically administrated vehicle, donepezil or different doses of herbal formula GAPT for 8 or 4 months. Three-month-old male C57BL/6 J mice was set as vehicle control. Results Immunohistochemistry analysis showed that there were CaMKII expression decrease in the CA1 region of APPV717I transgenic mice, while the CaMKII expression of donepezil or GAPT treated transgenic mice were all increased. And there were CaN expression increase in the brain cortex of APPV717I transgenic mice, while there were decrease of CaN expression in donepezil or GAPT treated transgenic group. Western blot analysis showed the similar expression pattern without significant difference. Conclusion GAPT extract have showed effectiveness in activating the expression of CaMKII and inhibiting the expression of CaN either before or after the formation of amyloid plaques in the brain of APPV717I transgenic mice, which may in certain way alleviated neuron synaptic dysfunction in AD.